2007
DOI: 10.1521/jscp.2007.26.6.728
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support, Malevolent Maternal Representations, and Older Adults' Depressed Mood

Abstract: We explored the associations between Malevolent Maternal Representations (ORI; Blatt, Chevron, Quinlan, Schaffer, & Wein, 1992) and levels of Depressed Mood among 147 community dwelling Israelis; older adults (ages 70-83) in good health, functioning well, and not requiring any form of assisted living. Depressed Mood was measured by the CES-D (Radloff, 1977) and the DACL (Lubin, 1965). High Malevolent Maternal Representations were associated with high levels of Depressed Mood; low perceived social support was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…In particular, they found that the relationship between pregnant women's internal working models and antenatal attachment to their infant was mediated by the future mother's representations of her own mother. Hence, from a clinical perspective, early attachment as well as current object relations both seem to express related, but not identical, aspects of internal working models (Besser & Priel, 2007; Priel & Besser, 2001) that have an important impact on postpartum adaptation. Congruent with Blum's (2007) assumptions, these psychodynamically inspired studies suggest that mother's own early attachment experiences and her perceptions of her own caregivers influence her attachment to her child and that this association is mediated by the mother's representations of early caring relationships, especially with her own mother (Fonagy, Gergely, & Target, 2007).…”
Section: The Transition To Motherhood From a Psychodynamic Perspectivementioning
confidence: 99%
“…In particular, they found that the relationship between pregnant women's internal working models and antenatal attachment to their infant was mediated by the future mother's representations of her own mother. Hence, from a clinical perspective, early attachment as well as current object relations both seem to express related, but not identical, aspects of internal working models (Besser & Priel, 2007; Priel & Besser, 2001) that have an important impact on postpartum adaptation. Congruent with Blum's (2007) assumptions, these psychodynamically inspired studies suggest that mother's own early attachment experiences and her perceptions of her own caregivers influence her attachment to her child and that this association is mediated by the mother's representations of early caring relationships, especially with her own mother (Fonagy, Gergely, & Target, 2007).…”
Section: The Transition To Motherhood From a Psychodynamic Perspectivementioning
confidence: 99%
“…Psychiatric patients have consistently demonstrated problematic conceptual themes, and a lack of cognitive complexity and differentiation in their descriptions of primary objects (Diguer et al, 2004). Punitive object representations have also been specifically linked with higher levels of depression and a decrease in perception of social support (Besser & Priel, 2007). There is also a close link between object representation and attachment style.…”
Section: Mental Health Religion and Culture 451mentioning
confidence: 99%